Acute kidney injury following hepatectomy and its impact on long-term survival for patients with hepatocellular carcinoma. Issue 5 (3rd October 2021) - Lee, K F; Lo, E Y J; Wong, K K C; Fung, A K Y; Chong, C C N; Wong, J; Ng, K K C; Lai, P B S
Abstract: Background: Acute kidney injury (AKI) is increasingly being recognized after hepatectomy. This study aimed to identify factors predicting its occurrence and its impact on long-term outcome among patients with hepatocellular carcinoma (HCC). Methods: This was a retrospective analysis of the incidence of AKI, factors predicting its occurrence, and its impact on patients undergoing hepatectomy between September 2007 and December 2018. A subgroup analysis included patients with histologically proven HCC. Results: The incidence of AKI was 9.2 per cent in 930 patients. AKI was associated with increased mortality, morbidity, posthepatectomy liver failure (PHLF), and a longer hospital stay. On multivariable analysis, study period December 2013 to December 2018, diabetes mellitus, mean intraoperative BP below 72.1 mmHg, operative blood loss exceeding 377ml, high Model for End-Stage Liver Disease (MELD) score, and PHLF were predictive factors for AKI. Among 560 patients with HCC, hypertension, BP below 76.9 mmHg, blood loss greater than 378ml, MELD score, and PHLF were predictive factors. The 1-, 3-, and 5-year overall survival rates were 74.1, 59.2, and 51.6 per cent respectively for patients with AKI, and 91.8, 77.9, and 67.3 per cent for those without AKI. Corresponding 1-, 3-, and 5-year disease-free survival rates were 56.9, 42.3, and 35.4 per cent respectively in the AKI group, and 71.7, 54.5, and 46.2 per cent in the no-AKI group. AKI was an independent predictor of survival in multivariable analysis. Conclusion: AKI is associated with longer hospital stay, and higher morbidity and mortality rates. It is also associated with shorter long-term survival among patients with HCC. To avoid AKI, control of blood loss and maintaining a reasonable BP (72–77 mmHg) during hepatectomy is important. Abstract : Acute kidney injury is associated with longer hospital stay, and higher morbidity and mortality rates. It is also associated with shorter long-term survival among patients with liver cancer. To avoid acute kidney injury, control of blood loss and maintaining a reasonable mean BP (72–77 mmHg) during hepatectomy is important.